(untitled) (Scientific journal of the Fergana State University, 2024)
‘Oxynoemacheilusʼ oxianus (Kessler, 1877), the only representative of its genus found in the water bodies of Uzbekistan, was recorded only in the part of the Amu Darya flowing through the Surkhandarya region. The article presents the O. oxianus population and its morphometric analysis in the canals and ditches of pumping stations (on the territory of the Termez Region) receiving water directly from the Amu Darya.